Schistidium relictum (Grimmiaceae, Bryophyta), a new moss species from Northwest North America and Siberia - Mcintosh, Terry T.; Blom, Hans H.; Kuznetsova, Oxana I.; Ignatova, Elena A. (Phytotaxa, 2017)
Schistidium relictum is described as a new northwest North American and Siberian species of moss. Important distinguishing characters include dull, nearly black plants, with stems densely and evenly foliated, weakly spreading leaves that usually lack awns, and the mostly 1-stratose distal leaf laminae with 2(–3) -stratose margins. The species has a remarkable disjunct distribution pattern with most of the sites where it has been found having been unglaciated during the Pleistocene glaciations. It is restricted to areas with occurrence of calcareous bedrock, especially limestones. It appears to be rather isolated genetically based on molecular studies of total ITS. It is sister to the large clade, ‘Apocarpum’, which consists of species which probably embody its closest known extant relatives.